2016
DOI: 10.12697/akut.2016.22.02
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of perceptual and physiological variables of running on a track, motorized treadmill, and non-motorized curved treadmill at increasing velocity

Abstract: The aim of this study was to compare perceptual and physiological variables between running on three different modalities -an indoor athletics track, a motorized treadmill, and a non-motorized curved treadmill -for 1000 m at three different velocities. Ten male athletes (age 24±3 years, body mass 69.8±6.91 kg, height 1.80±0.06 m, VO2peak 69.0±6.70 ml/kg/ min) conducted three 1000 m laps at increasing velocity on three different running modalities. The athletes had a 3-minute recovery between each lap, where th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…slower 5 km and 1-h time trials) on a motorised treadmill compared with overground running [16,20]. Consistent with findings of poorer endurance running performance, some studies have reported that motorised treadmill running is perceived as requiring greater effort than overground running [14] and runners select slower running speeds on a motorised treadmill than overground when instructed to run at a fixed level of perceived effort [21].…”
Section: Key Pointsmentioning
confidence: 85%
See 4 more Smart Citations
“…slower 5 km and 1-h time trials) on a motorised treadmill compared with overground running [16,20]. Consistent with findings of poorer endurance running performance, some studies have reported that motorised treadmill running is perceived as requiring greater effort than overground running [14] and runners select slower running speeds on a motorised treadmill than overground when instructed to run at a fixed level of perceived effort [21].…”
Section: Key Pointsmentioning
confidence: 85%
“…Thirty-four studies were included in this review and are summarised in Table 2. Non-motorised treadmill running was considered in only three of the 34 included studies [5,14,29]. This small number of studies was considered insufficient for undertaking a systematic review.…”
Section: Search Resultsmentioning
confidence: 99%
See 3 more Smart Citations